Location Orientation of Organic Stores in Low Demand Areas: A Case Study of a Niche Market - Gultekin, Beyza; . Ana Espinosa SeguÃ (Information Management and Business Review, 2013)
This research provides a case study of a niche market in Marina Alta and Marina Baja counties located on the coast of the province of Alicante, Spain. These counties attract foreign residents from Germany, United Kingdom, and Scandinavia who are the frequent consumers of organic products. Accordingly, retailers choose the store location based on demand for organic products and detects a niche market in Spain. In addition, the study reveals the consumption patterns of organic-oriented consumers. In-depth interview is conducted with store managers and a researcher-administered survey is applied to the customers to identify the market. The study reveals the relationship between the presence of foreign residents who are more familiar to organic products and organic retailers’ choice of store location. Results are given and discussed.